In vitro Quality Analysis of Different Brands of Alprazolam Tablet Available in Bangladesh (Bangladesh Pharmaceutical Journal, 2015)
Alprazolam is a benzodiazepine anxiolytic commonly prescribed as a sleeping aid and for the treatment of anxiety disorders. The current study was undertaken with the aim of analyzing quality of commercially available brands of alprazolam tablets available in Bangladesh. To assess the quality, locally available 0.25 mg alprazolam tablet of seven different manufacturers were selected and certain physico-chemical parameters like weight variation, hardness, friability, disintegration time and dissolution profile etc. were evaluated using in-vitro analytical methods. All the tablet brands met the requirements of British Pharmacopoeia as they showed acceptable weight variation and friability (below 1%). Brands were slightly different in hardness, disintegration time and dissolution profile from each other. The hardness of all the brands was found to be in the range of 1.50±0.18 to 4.21±0.11 kg-ft. In water medium the disintegration time of all brands were found to be 0.57±0.45 to 2.22±0.23 min. Five out of seven brands showed better dissolution profile as they released more than 90% drug in 30 min. The study revealed that most of the marketed alprazolam tablets met the BP standards for physico-chemical properties which are the indicators of drug quality. It can be concluded that drug products should always comply standard quality parameters that are the prerequisites for getting satisfactory clinical effects. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22302 Bangladesh Pharmaceutical Journal 16(2): 185-188, 2013